Inhibitory Effect of Glycosaminoglycans on Human Mast Cell Stimulation by IL-33 - Gross, Amanda. (Tufts University. Tisch Library., 2019)
Glycosaminoglycans (GAGs) are linear, highly negatively charged carbohydrate chains present in connective tissues, primarily known for their functional role in connective tissue, joint lubrication and anticoagulant activity. Chondroitin sulfate (CS) and heparin (Hep) are also found in the numerous secretory granules of mast cells (MC), hematopoietic tissue immune cells involved in allergic and inflammatory reactions, and are thought to store biogenic amines, such as histamine, due to their negative charge. It was previously shown that CS and Hep may inhibit secretion of histamine from rat connective tissue MC, but their effect on human MC remains unknown. Immortalized human LAD2 MC were pre-incubated with CS before stimulation by either the peptide substance P (SP, 2 µM) or the cytokine IL-33 (10 ng/mL). The data indicated that pre-incubation with CS had no detectable effect on MC degranulation stimulated by SP, but significantly inhibited TNF and CXCL8 secretion from LAD2 MC stimulated by SP or IL-33. In order to determine if the molecular weight (MW) and structure affected the inhibitory activity of GAGs, the effects of MC pre-incubation with Hep or dermatan sulfate (DS) on mediator secretion from MC stimulated with IL-33 were studied. DS and Hep, both unfractionated (UF) and low molecular weight (LMW), inhibited IL-33-stimulated secretion of TNF and CXCL8 to a similar extent as CS. Studies were conducted at 4°C and 37°C to determine if fluorescein-conjugated CS (CS-F) was taken up at a physiologically relevant temperature. LAD2 MC associated with CS-F only at 37°C, but not 4°C, indicating its uptake. In further pursuit of determining the mechanism of inhibitory action of GAGs on MC stimulated with IL-33, gene expression of TNF and CXCL8, intracellular calcium ion influx, as well as effect on expression of the IL-33 surface receptor, ST2, were carried out. None of the GAGs tested had any effect of these processes. Neutralization of the hyaluronan receptor CD44 did not detectably affect the uptake of CS-F. To determine if CS interferes with proteins associated with vesicle fusion, the effect of CS on fluorescence associated with soluble N-ethylmaleimide-sensitive factor attachment protein (SNAP) receptor (SNARE) was investigated. CS appeared to interfere with the fluorescence associated with the SNARE protein SNAP-23, but not VAMP-8, in LAD2 MC. In contrast to the LAD2 cells stimulated by IL-33, GAGs did not detectably affect TNF or CXCL8 secretion from primary hCBMC stimulated with IgE/anti-IgE. The data here suggest that GAGs can inhibit secretion of TNF and CXCL8 from human mast cells stimulated by IL-33, a crucial alarmin involved in inflammation. GAGs from the tissue microenvironment or secreted by MC, themselves, upon activation, could inhibit the secretion of mediators from MC in an autocrine fashion. GAGs could be formulated for systemic or topical treatment of allergies or inflammation.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Pharmacology & Experimental Therapeutics.; Advisor: Theoharis Theoharides.; Committee: Angelo Azzi, John Castellot, Athar Chishti, and Laura Liscum.; Keywords: Pharmacology, Immunology, and Cellular biology.